1975
DOI: 10.1159/000458984
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Free and Conjugated Bile Salts on α-Amylase Activity

Abstract: The effect of individual bile salts on aamylase hydrolysis of Cibachron Blue starch was studied at pH 6.0. With sodium cholate, taurocholate and taurodeoxycholate, enzyme activity was increased to 150-160% of the control value, at a concentration of ~1 mmol/1 bile salt. The increased activity extended up to 4 mmol/1. The bile salts sodium deoxycholate and taurochenodeoxycholate exerted activation and inhibition depending on the concentration. With deoxycholate (0.75 mmol/1), activation (150%) was evident, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1976
1976
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The concomitant elevation of cysteine and taurine levels in the chyme observed in our previous experiment, indicates that MCT may also stimulate bile secretion (Nordrum et al 2000). As bile acids have the ability to activate or stabilize digestive enzymes (Malagelada et al 1973; Donnell et al 1974), stimulating effect of MCT on enzyme activity may partly be the result of increased stability. These considerations regarding the results of our previous study seem valid for the results of the present experiment as well, showing increased activities of proteolytic enzymes with increasing MCT level and higher water content of the chyme.…”
Section: Effects Of Mctmentioning
confidence: 99%
“…The concomitant elevation of cysteine and taurine levels in the chyme observed in our previous experiment, indicates that MCT may also stimulate bile secretion (Nordrum et al 2000). As bile acids have the ability to activate or stabilize digestive enzymes (Malagelada et al 1973; Donnell et al 1974), stimulating effect of MCT on enzyme activity may partly be the result of increased stability. These considerations regarding the results of our previous study seem valid for the results of the present experiment as well, showing increased activities of proteolytic enzymes with increasing MCT level and higher water content of the chyme.…”
Section: Effects Of Mctmentioning
confidence: 99%
“…In this regard, several possible hypotheses have been put forward. It may play an anchoring role (enabling amylase to remain seated on the starch substrate) such that multiple attacks may occur (Robyt & French, 1970a,b;Thoma, Spradlin & Dygert, 1971) or it may have a regulatory function (O'Donnell, McGeeney & Fitzgerald, 1975). The second substrate-binding site between the A and C domains (Payan et al, 1980;Buisson et al, 1987) is far away from the main substrate-binding site.…”
Section: Comparison Of Human Salivary and Pancreatic Amylasesmentioning
confidence: 99%
“…The rapid binding was supported by the results in Figures , , , and that bile salt-dependent inhibition of starch/iodine complex formation was observed when iodine solution was added within 1 min after the preparation of the mixture of starch and bile salts. Bile salts have been reported to be able to enhance and inhibit the amylase-catalyzed digestion at low (<1 mM) and high concentrations, respectively . The results of the present study suggest that the concentration of bile salts in bile (1–10 mM) could inhibit starch digestion in the small intestine.…”
Section: Resultsmentioning
confidence: 50%
“…It has been reported that isoflavones bind to receptors of a steroid hormone estrogen. , The results prompted us to postulate that bile salts (Figure ) might also bind to starch to inhibit its digestion by amylase. Many studies have been conducted on the binding of bile salts to polysaccharides, but only one study concerns the effect of bile salts on amylase-catalyzed digestion of starch …”
Section: Introductionmentioning
confidence: 99%